PEMBAYARAN HUTANG MELALUI HASIL PENJUALAN UBI PRESPEKTIF FIQH MUAMALAH (Studi Kasus di Jorong Sungai Jambu Nagari Sungai Jambu Kecamatan Pariangan Kabupaten Tanah Datar) - Zulkifli W; Fitri Yeni Dalil (Institut Agama Islam Negeri Batusangkar, 2021)
This study examines the implementation of the debt agreement of sweet potato farmers with toke yam, the mechanism for payment of money owed by sweet potato farmers to toke yam and a review of muamalah fiqh on the implementation of conditional debt and debt payment mechanisms according to muamalah fiqh. The type of research used is field research (field research). The findings of this research are, first, the implementation of debt between sweet potato farmers and sweet potato farmers, namely Toke gives debt to farmers on the condition that farmers must sell their sweet potato harvests to Toke and Toke buys the sweet potatoes at a price set by Toke himself. Second, the mechanism for payment of debt between farmers and toke ubi is through the sale of sweet potatoes which are cut directly by toke ubi as a form of debt payment. Third, the implementation of debts between farmers and tokens is contrary to the tabarru contract and in buying and selling there is an element of coercion or lack of willingness and toke to take profits that are not their rights.